Feature profile simulation of silicon nitride atomic layer deposition. (26th May 2017) - Moroz, Paul; Moroz, Daniel J.
Abstract: We perform feature-scale numerical simulations with the FPS3D software package to model the atomic layer deposition of silicon nitride using cycles of hexachlorodisilane and hydrazine. Whenever available, the results of simulations are compared with the published experimental data. These simulations emphasize the power of a feature-scale approach, which is effective even for atomic layer deposition, a delicate method of materials processing. We demonstrate reasonably good agreement with the results of experiments. Based on simulations, we suggest some explanations of important phenomena such as the increase in surface roughness as the number of processing cycles increases, the rounded corners of deposited film, the small amount of impurities in the film comprised of elements of the processing gases, and the observation that typically less than a full monolayer of film is deposited per cycle.